Proceedings of 1994 VLSI Technology Symposium
DOI: 10.1109/vlsit.1994.324444
|View full text |Cite
|
Sign up to set email alerts
|

Experimental 2.0 V power/performance optimization of a 3.6 V-design CMOS microprocessor-PowerPC 601

Abstract: Eoxidc (MV/cm) V r -.jJV) V rp j J V ) Experimental 2.0V Power/Performance Optimization of a 3.6V-Design CMOS Microprocessor -PowerPC 601 3.1 3.3 3.6 0.60 0.34 0.24 -0.80 -0.76 -0.55Abstract An experimental 2.0V PowerPC 601* microprocessor demonstrating 3X active power reduction and performance compara6le to the 3.6V version has been fabricated. The standard 3.6V 0.6pm CMOS technology was modified for low-power operation with unmodified circuits/masks. No degradation to yield was observed. Experimental low-vol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…To meet the market need, a CMOS-technology scaling technique has been demonstrated at the IBM Microelectronics chip fabrication facility in Essex Junction, Vermont [3]. This approach may allow microprocessor developers to radically reduce the power consumption of a CPU without sacrificing performance, reliability, or yield, or incurring excessive development expense.…”
Section: Introductionmentioning
confidence: 99%
“…To meet the market need, a CMOS-technology scaling technique has been demonstrated at the IBM Microelectronics chip fabrication facility in Essex Junction, Vermont [3]. This approach may allow microprocessor developers to radically reduce the power consumption of a CPU without sacrificing performance, reliability, or yield, or incurring excessive development expense.…”
Section: Introductionmentioning
confidence: 99%
“…A recent experiment demonstrated that a 3.5X power reduction in a high-performance, 0.6pm CMOS product technology, could be achieved with only minor process changes and the same mask set [3]. For the IBM 3.6V PowerPC 1601 microprocessor, an existing, wellcharacterized product was selectively scaled in thresholds and gate oxides.…”
Section: Selective Scalingmentioning
confidence: 99%